(untitled) (Orinoquia, 2018)
Chronic wounds are considered a challenge for the of health providers network and train health professional institutions because they demand comprehensive approach to the people who suffer from them, a highly qualified human talent for nursing in the use of advanced technology. Objective: to Determine the knowledge of nursing professionals in the use of advanced technology for the management of chronic wounds in health institutions in Villavicencio – Meta. Equipment and Methods: Quantitative, descriptive, quasi-experimental cross-sectional study, with measurement before and after intervention. Sample: Intentional (n=37) Nursing professionals with more than three months of work and with responsibility in chronic patient care. Instrument designed by the researchers. A training plan was planned and developed to update the participants to a face to face. The data were processed in SPPSS version 23 and counted with the approval of the Institutional Ethic Committee and the informed consent of the participants. Results: 83.8% women, average age of 37 years, 11,2% average experience age, 56,8% with previous training in wound healing, the chronic wounds with more frequent care are open abdomen, diabetic foot ulcers and pressure ulcers, 83,7% with low and medium level knowledge about the characterization of wounds before the intervention and in the measurement of the knowledge of the use of advanced technology for the treatment of chronic wounds after the training there is an increase of 3,6 points in the measurement, statistically significant P<0.05 Thetraining process promoted knowledge about the use of technology in the participating professionals and highlights the need to continue with ongoing training in the care of patients with chronic wounds and the updating of the protocols of health service providers.